2015
DOI: 10.1086/682278
|View full text |Cite
|
Sign up to set email alerts
|

An Active East Asian Monsoon at the Oligocene-Miocene Boundary: Evidence from the Sikouzi Section, Northern China

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. The University of Chicago Press is collaborating with JSTOR to digitize, preserve and extend access to The Journal of Geology. A B S T R A C TThe East Asian monsoon forms a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…15–13 Ma) with the establishment of a permanent Antarctic ice‐sheet (Zachos et al, 2008; Liu et al, 2009; Beddow et al, 2016; Hutchinson et al, 2021). These periods coincided with the emergence of seasonal biomes in Europe and Asia, the aridification of Australian, African, and Asian inlands, and the subsequent contraction of the tropics with tropical forests retreating to lower latitudes (Morley, 2003; Bowen, 2007; Contreras et al, 2013; Fang et al, 2015; Lin et al, 2015; Beasley et al, 2021; Couvreur et al, 2021). Moreover, all above geo‐climatic changes, associated with sea level drops, have led to major turnovers of the vegetation (Sun et al, 2015; Pound & Salzmann, 2017; Couvreur et al, 2021), with successful plant dispersal across different paleogeographic regions (Jiang et al, 2019), and the establishment of present‐day genera and families in multiple regions, probably pre‐adapted to current climates (e.g., Linnemann et al, 2017; Su et al, 2018; Huang et al, 2021; Ling et al, 2021).…”
Section: Discussionmentioning
confidence: 97%
“…15–13 Ma) with the establishment of a permanent Antarctic ice‐sheet (Zachos et al, 2008; Liu et al, 2009; Beddow et al, 2016; Hutchinson et al, 2021). These periods coincided with the emergence of seasonal biomes in Europe and Asia, the aridification of Australian, African, and Asian inlands, and the subsequent contraction of the tropics with tropical forests retreating to lower latitudes (Morley, 2003; Bowen, 2007; Contreras et al, 2013; Fang et al, 2015; Lin et al, 2015; Beasley et al, 2021; Couvreur et al, 2021). Moreover, all above geo‐climatic changes, associated with sea level drops, have led to major turnovers of the vegetation (Sun et al, 2015; Pound & Salzmann, 2017; Couvreur et al, 2021), with successful plant dispersal across different paleogeographic regions (Jiang et al, 2019), and the establishment of present‐day genera and families in multiple regions, probably pre‐adapted to current climates (e.g., Linnemann et al, 2017; Su et al, 2018; Huang et al, 2021; Ling et al, 2021).…”
Section: Discussionmentioning
confidence: 97%
“…The initiation of the EASM was suggested to be at the O–M boundary based on multiple lines of evidence, such as the compilation of paleobotanical and lithological data from 125 sites over China (Sun & Wang, ) and the weathering records from the South China Sea (Clift et al ., ). Different investigations based on the sedimentological and pollen records spanning the last 20 Ma from the Sikouzi section (Ningxia, China) similarly concluded that the EASM was active around the O–M boundary (Jiang & Ding, ; Lin et al ., ). Recently, the evolutionary dynamics of the late Cenozoic genus Fupingopollenites have also indicated the existence of EASM during the early Miocene (Miao et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Some have suggested that the onset or intensification of the EASM occurred at the Oligocene–Miocene (O–M) boundary ( c . 23 million yr ago (Ma); Sun & Wang, ; Clift et al ., ; Lin et al ., ), probably related to the uplift of the northern Tibetan Plateau (TP) (Tada et al ., ). However, others have argued that the monsoonal climate involving the EASM was established as early as the Eocene (Quan et al ., ; Wang et al ., ; Licht et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…3). The LAR describing the accumulation of EAEBLF‐characteristic genera showed two sequences of rapid speciation events at the Oligocene–Miocene (25.2 Ma, the lower peak) and the Miocene–Pliocene boundaries (6.4 Ma, the higher peak), which coincided with two intensification periods of the Asian monsoon at the Oligocene–Miocene boundary (25–20 Ma) and from the middle Miocene to the Pliocene (15–4 Ma) (Sun & Wang, 2005; Guo et al ., 2008; Yao et al ., 2011; Lin et al ., 2015; Tada et al ., 2016; Spicer, 2017; Farnsworth et al ., 2019). The diversification of numerous lineages directly contributed to the lower peak (Nie et al ., 2008; Zhang et al ., 2011; Yu et al ., 2017; Deng et al ., 2018; Chen et al ., 2020; Zhu et al ., 2020), whereas the higher peak was consistent with the origin or the diversification rate shift (Yu et al ., 2017; Deng et al ., 2018; Chen et al ., 2020) discovered in other lineages.…”
Section: Discussionmentioning
confidence: 99%